Diagnose and Treatment of ADHD in Adult Woman: A Literature Review - Sulistiawangi; Murniati, Rinesita; Sholihatin, Illiyani; Khalda, Yumna Iftinan (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Most of the women remain undiagnosed until adulthood in ADHD. The gap on incidence ratio of ADHD between girls and adult women clearly reflects that there are different characteristics of ADHD symptoms in women, particularly a tendency towards inattentiveness, which usually goes unnoticed until adulthood. The delayed diagnosis may affect quality of life, life dissatisfaction, anxiety, substance addiction, social problem, depression, and suicide tendencies. Attention Deficit/Hyperactivity Disorder is a neurodevelopmental disorder predestined with the symptoms of difficulty in maintaining attention, hyperactivity, and impulsive behavior, probably caused by genetic, neurobiologic, and environmental factors. The aim of this study is to understand the characteristics of ADHD symptoms look like in adult women and how to treat it. The method this study uses is a literature review sourcing articles from journal databases such as PubMed, Google Scholar, and ResearchGate. Research findings have established the fact that stigma and gender bias could obscure or delay the diagnosis of ADHD in women. Consequently, they often suffer from mental health issues, problems in relationships with others, and comorbid conditions like depression and anxiety that complicate the diagnosis of their ADHD. Treatment approach might differ for women because hormonal fluctuations during the menstrual cycle can exacerbate symptoms of ADHD.